Value Co-Creation Model of Halal Logistics Services - Liane Okdinawati; Togar M. Simatupang; Arif Imran; Yuliani Dwi Lestari (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
Increasing consumer awareness to provide halal assurance in the supply chain process happens in Muslim countries and non-Muslim countries. Kosher products become a symbol for food safety, quality assurance, and lifestyle choice due to the strict requirements, thereby reducing the risk of contamination of the disease. This led to the increase of demands of halal logistics services to implement the halal concepts in logistics processes. One of the obstacles faced by the companies is a lack of understanding of how the halal concept is applied in accordance with the role of each company in the supply chain. This paper illustrates the value co-creation model using several supply chains for Fast-moving consumer goods (FMCG), cosmetics, fashion, and pharmaceuticals to provide value for customers and all parties that guarantee halal concepts throughout the activities of the supply chains. Business model and the adaptation in operational planning for a transportation company as halal logistics services are also developed in this paper by including segregation process, packaging, cleaning process, halal labeling, and halal documentation to ensure standard halal assurance are distinguished from activities in the general logistics process.